Technology Transfer of Humidity and Temperature Control System Using Ultrasonic Mist Maker in the Lamongan Hydroponic Farm Area, Sidoharjo Lamongan District - Aris Widodo; Uswatun Chasanah; Garist Sekar Tanjung (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Lamongan Hydroponic Farm's vegetable farming has a lot of potential, however managing humidity and temperature is a problem. While farmers there have been successful in creating fruitful hydroponic gardens, they struggle to keep the ideal growing environment. Severe temperature and humidity swings have an impact on harvest quality and raise production costs. The community service team suggested using solar energy and ultrasonic mist maker technologies to solve this issue. It is anticipated that this technology will lower operating costs, produce the perfect atmosphere for plant growth, and automatically control the amount of water in the air. Lamongan hydroponic farming may therefore be more productive and long-lasting. Lamongan Hydroponic Farm's community service program is implemented through the following phases: socializing, training, technology application, mentorship, and program sustainability evaluation. Two key technologies were developed as a result of this process: smart agricultural knowledge and ultrasonic mist makers with IoT and solar panel systems attached. According to the evaluation results, the three pretest and posttest questionnaires received resulted in an average improvement in partner knowledge from 49% to 74%.